Hasil Pengukuran Kadar Asam Urat Menggunakan Point of Care Testing (POCT) dan Gold Standard (Chemistry Analyzer) (Journal of Telenursing (JOTING), 2021)
This study aims to determine the results of measuring uric acid levels using POCT and chemistry analyzer as the gold standard simultaneously. The research method used was cross-sectional with a sample of 47 adults at Harapan and Doa Hospital, Bengkulu City. The sample selection was based on non-probability consecutive sampling. The results showed that the uric acid level as measured by POCT and Chemistry analyzer was 6.2 mg/dL. The subjects of hyperuricemia detected on the POCT device were 20 people, while on the chemistry analyzer, there were 21 people. In conclusion, the results of measuring uric acid levels using POCT obtained fewer gout sufferers than using a Chemistry Analyzer.Keywords: Gout, Chemistry Analyzer, POCT